La Asociatividad y los emprendimientos en el cantón Cumandá, provincia de Chimborazo período 2018. - Gabriela Elizabeth, Estrada Cabezas (2020)
The present research work entitled “The Associativity and Entrepreneurships in the Canton Cumandá, province of Chimborazo period 2018” aims to identify how the associativity influences the enterprises, it is for this reason that data collection was performed to analyze the information and establish a solution to the problem. The research method used is the hypothetical-deductive, the research is of the type; descriptive because it describes the reality of a situation, documentary because reports were used to obtain information and field since surveys were carried out on the representatives of the Cumandá Canton ventures. The population was conformed by the 605 ventures, which when calculating the sample, resulted in 236 people surveyed. The results obtained by analyzing the information of the data collected, it was identified that the associativity influences the enterprises, so a strategic planning model has been proposed to improve the associativity process of the different associations already established and used as the basis for the new ones to be created.